The Next Frontier of Green Building Certifications: Evaluating the Future of LEED, BREEAM and WELL Standards - Khan, Hasibullah; Safi, Samiullah (Journal of Engineering and Applied Sciences Technology, 2025)
Green building certifications have become a cornerstone in sustainable architecture and urban planning. As environmental concerns escalate and regulatory frameworks evolve, certification systems such as Leadership in Energy and Environmental Design (LEED), Building Research Establishment Environmental Assessment Method (BREEAM), and WELL Building Standard are adapting to new challenges. This study evaluates the current impact, limitations, and future trends of these certification programs. It explores emerging factors such as climate resilience, digital integration, and holistic sustainability to forecast how green building certifications will evolve in the coming decades.